Preventing Corruption in the Customs of Afghanistan - Baryal, Baryalai; Patang, Ghazi; Sharaf, Sharafdin (Integrated Journal for Research in Arts and Humanities, 2022)
Afghanistan's customs corruption has dramatically increased during the past few years. The purpose of the article is to identify the main causes of corruption in customs and develop effective policies to reduce and prevent corruption. Interviews with customs employees, producers, hiring managers, consumers, trade union representatives, and government representatives have been conducted to collect relevant data and information, using their reports from the relevant ministries, and some national and international organizations. Analysis of the received data shows that prevention of the intervention of central, and provincial officials, members of the National Assembly, and warlords, anti-discrepancy in customs duties, reduction of many oversight bodies in Afghanistan’s customs and tax departments, and use of the central customs control system Knowing the factors will help adopt effective policies to reduce and prevent corruption in the customs of Afghanistan. This article hopes to offer a number of ways that will have a positive effect on the relationship between government and people, increase government revenue, remove budget deficit, and play an important role in the country's economic development.